Politik Hukum Penetapan Baku Mutu Lingkungan sebagai Instrumen Pencegahan Pencemaran Lingkungan Hidup - Ade Arif Firmansyah; Malicia Evendia (Universitas Syiah Kuala, 2014)
The standard of environmental quality is one of the instruments in preventing environmental pollution beside KLHS, special plan, environemtal analysis, UKL-UPL, permission, etc. the standard comprises of the standards of water, water waste, sea water, air ambien, emission, and nuisance. Politics of law in determination of the standards as a preventive instrument of the pollution is based on Article 28H verse (1) of the Indonesian Constitution 1945 states that healthy and good environment is a human rights that should be guaranteed, Article 33 of the Act also provides that national economy must be based on economic democracy by environmentally principle. The determination is one of the legal responsive forms raised from democracy politics configuration to answer the need of people for the healthy and good environment. The determination in the statutes as legal subtances must be followed by structural development and legal culture hence the environment quality for sustainable life exists. Politics of Law in The Environmental Quality Standard Determination as An Instrument in Environmental Polution Prevention